Stakeholder influence on health and safety controls - Wijesinghe, D.N.; Samudrage, D.; Gunarathne, N. (Proceedings of the 20lh Conference of the Environmental and Sustainability Management Accounting Network (EMAN), Liineburg, 2016, 2016)
Attached

U sing th e levers o f co n tro l m odel, this p aper investigates how p rim a ry stakeholders in flu e n ce the introduction o f organ iza tio n a l health a n d sa fety strategies w hile im proving o rganizational m a n a g e m e n t control system s. These p ressures to em bed interactive m o d e o f controls help m anagem ent to create a dialogue with the em ployees, w hich in turn can change the diagnostic controls, boundary system s a n d b e lie f system s.